Suprascapular neuropathy in the setting of rotator cuff tears: study protocol for a double-blinded randomized controlled trial. Issue 1 (December 2016) - Sachinis, Nikolaos; Boutsiadis, Achilleas; Papagiannopoulos, Sotirios; Ditsios, Konstantinos; Christodoulou, Anastasios; Papadopoulos, Pericles
Abstract Background It has been indicated that rotator cuff tears, especially large or massive ones, can cause suprascapular neuropathy. When such a diagnosis has been established, it is still unknown whether an arthroscopic release of the superior transverse scapular ligament during cuff repair can change the course of this neuropathy. Methods/design This is a single-center, double-blinded randomized controlled trial for which 42 patients with large or massive repairable rotator cuff tears and suprascapular neuropathy will be recruited and followed up at 6 and 12 months. Nerve function will be measured by nerve conduction and electromyography studies preoperatively and at the selected follow-up periods. Patients will be randomly divided into equally numbered groups, the first one being the control group. Patients of this group will undergo arthroscopic repair of the rotator cuff without combined arthroscopic release of the superior transverse scapular ligament; in the second group the ligament will be released. The primary objective is to test the null hypothesis that arthroscopic repair of large/massive rotator cuff tears in patients with combined suprascapular neuropathy provides equivalent outcomes to one-stage arthroscopic cuff repair where the superior suprascapular ligament is additionally released. The secondary objective is to search for a relation between rotator cuff tear size and degree of suprascapular nerve recovery. The tertiary objective is to demonstrate any relation between rotator cuff muscle fatty infiltration grade and degree of suprascapular nerve function. Patients, clinicians during follow-up clinics and the neurologist will be blinded to the type of surgery performed. Discussion To the best of our knowledge, we are unaware of any prospective, randomized double-blinded studies with similar objectives. So far, the evidence suggests a positive correlation between massive rotator cuff tears and suprascapular neuropathy. However, there is mixed evidence suggesting that neuropathy can be effectively treated with rotator cuff repair with or without release of the superior transverse scapular ligament. Trial registration ClinicalTrials.gov registration numberNCT02318381 ; date of initial release: 5 December 2014.